2021
DOI: 10.1128/aac.02180-20
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Superoxide Dismutase Confers Enhanced Reactive Oxygen Species-Mediated Eradication of Polymyxin B-Induced Acinetobacter baumannii Persisters

Abstract: Bacterial persisters represent non-inheritable drug tolerant population that are linked to recalcitrance of infections in healthcare settings. The rise of antibiotic resistance and depletion of new antibiotics in drug discovery pipeline has made the task of persister eradication more daunting. In the present study, we report that treatment of Acinetobacter baumannii with the last resort antibiotic polymyxin B displays continuous variation in tolerance among different clinical isolates. Mechanistically, Polymyx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…A. baumannii has a variety of drug resistance mechanisms, including beta-lactamase, efferent pump activation and overexpression, membrane permeability reduction, change of penicillin binding protein, and enzymatic modification of aminoglycosides. The main mechanism of drug resistance to hydrocarbapenes is hydrocarbapenase production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A. baumannii has a variety of drug resistance mechanisms, including beta-lactamase, efferent pump activation and overexpression, membrane permeability reduction, change of penicillin binding protein, and enzymatic modification of aminoglycosides. The main mechanism of drug resistance to hydrocarbapenes is hydrocarbapenase production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the previous report, we found that the combination of colistin with azithromycin resulted in superior ll OPEN ACCESS iScience Article bactericidal effects to those of the individual drugs. It has been demonstrated that ROS facilitates the killing of bacteria by antibiotics and elimination of bacterial persister cells (Dubey et al, 2021). Upon encountering bacteria, neutrophils promptly generate ROS (Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of 1 mL of bacterial suspension containing the indicated concentration of rafoxanide or colistin alone or in combination or 100 µM CCCP per se . Incubation for 1 h, then the fluorescence was monitored at excitation/emission of 525/600 nm at 37°C with a luminometer (Varioskan Flash; Thermo Scientific) ( 16 ).…”
Section: Methodsmentioning
confidence: 99%